(untitled) (American Journal of Islam and Society, 2006)
The purpose of this essay is to compare the views of the Ikhwan al-Safa’, Isfahani, and Ibn Khaldun on labor, not to trace their influences, which would require separate treatment. However, we could presume the direct or indirect influence of figures such as the Ikhwan al-Safa’. A study into the attitudes toward labor is important for understanding a society’s economic rise or decline.